Before Learning the Code: A Commentary on Sargiani, Ehri, and Maluf (RRQ, 2022). Issue 1 (23rd November 2022) - Guo, Teng; Vazeux, Maria; Doignon‐Camus, Nadège; Bosse, Marie‐Line; Mahé, Gwendoline; Zagar, Daniel
Abstract: In this commentary, we argue the importance of the period before learning the alphabetic code and develop a new theoretical framework for the cognitive processes involved at the very beginning of learning to read. According to our theory, prereaders begin to learn to read by associating letter clusters with concrete phonological units such as syllables, a process we refer to as "building the syllabic bridge" (Doignon‐Camus & Zagar, 2014). This procedure may trigger statistical learning to extract regularities of grapheme–phoneme correspondences. We assume that statistical learning facilitates access to phonemic awareness and then the acquisition of the alphabetic code. Our arguments are partly based on the comparison between the studies conducted by Vazeux et al. (2020) and Sargiani et al. (2022), whose results might have seemed contradictory at first sight. Finally, we suggest pedagogical implications and some perspectives for future research. Abstract : In this commentary, we argue the importance of the period before learning the alphabetic code and develop a new theoretical framework for the cognitive processes involved at the very beginning of learning to read. According to our theory, prereaders begin to learn to read by associating letter clusters with concrete phonological units such as syllables, a process we refer to as "building the syllabic bridge" (Doignon‐Camus & Zagar, 2014).